ASAS J071404+7004.3 – a close, bright nova-like cataclysmic variable with gusty winds. Issue 3 (16th December 2021) - Inight, K; Gänsicke, B T; Blondel, D; Boyd, D; Ashley, R P; Knigge, C; Long, K S; Marsh, T R; McCleery, J; Scaringi, S; Steeghs, D; Thorstensen, J R; et al.
ABSTRACT: Despite being bright ( V ≃ 11.8) and nearby ( d = 212 pc) ASAS J071404+7004.3 has only recently been identified as a nova-like cataclysmic variable. We present time-resolved optical spectroscopy obtained at the Isaac Newton and the Hiltner and McGraw-Hill Telescopes, together with Swift X-ray and ultraviolet observations. We combined these with TESS photometry and find a period of 3.28 h and a mass transfer rate of 4\!-\!9× 10^-9 M_ yr^-1 . Historical photometry shows at least one low state establishing the system as a VY Scl star. Our high-cadence spectroscopy also revealed rapidly changing winds emanating from the accretion disc. We have modelled these using the Monte Carlo python code and shown that all the emission lines could emanate from the wind – which would explain the lack of double-peaked lines in such systems. In passing, we discuss the effect of variability on the position of cataclysmic variables in the Gaia Hertzsprung–Russell diagram.